Nanohybrid delivery systems for release of an anti-inflammatory drug based on the magnetic nanocomposites of Mg/Zn-Al layered double hydroxides - Sorour Bakhshi Sichani; Mohammadreza Mansournia; Fereshteh Abbasi (Results in Chemistry, 2025)
This research presents a novel approach to prepare the MgAl and ZnAl layered double hydroxides (MgAl-LDH (ML) and ZnAl-LDH (ZL)) as the shell on the core of Fe3O4 nanoparticles, followed by investigating the intercalation process of an anti-inflammatory drug, mefenamic acid (mef), and then, utilizing the produced Fe3O4@MgAl-LDH (FML) and Fe3O4@ZnAl-LDH (FZL) samples in a nanohybrid delivery model. The obtained biocompatible nanostructures were characterized by a range of techniques such as FT-IR, XRD, EDX, SEM, VSM, TEM, and TGA. The enlargement of the interlayer space, revealed by the X-ray diffraction technique, indicated that mef was successfully intercalated into the LDH nanostructures (ML 95.16 %, ZL 95.21 %, FML 93.88 %, and FZL 94.17 %). The surface morphology, examined by the scanning electron microscope images showed the stacked sheet of LDHs. In addition, the drug release properties were studied in PBS buffer (pH = 7.4) at 37 °C and exhibited a sustained release profile. The great rate of 80.03 %, 60.96 %, 82.11 %, and 80.55 % was found after 24 h for ML-mef, ZL-mef, FML-mef, and FZL-mef nanohybrids, respectively. The results revealed that the as-synthesized nanocomposites can play the role of a promising nanocarrier in the targeted and controlling drug release systems.